Digitalization Strategies at Türkiye’s Ro-Ro Ports: A SWOT-FAHP Analysis Approach - YORULMAZ, Murat; CANBAZ, Ömer; SEVINC BASOL, Figen; TAŞ, Ayşe (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Ports aim to restructure terminal operations and address problems to attain better design and efficiency. Recently, digitalization has been the most critical tool for both the management and development of terminal processes. Nonetheless, the feasibility of such a transition is dependent on a clear grasp of the factors influencing digitalization and recognizing their importance. This development also underlines the need for terminal-specific strategies and research. In the study, a research model using SWOT-FAHP was followed and conducted to apply an important scale to 71 SWOT criteria using a survey technique, resulting in a final set of 24 criteria. With expert assessments, a total of 16 strategy themes has been developed for the digitalization strategy matrix of Ro-Ro terminals. In this matrix, four development strategies have been identified: strengths-opportunities (SO) ‘adaptation to new technologies internationally’ and weaknesses-opportunities (WO) ‘employees’ adaptation to modern technology’. A total of four development strategies has been identified for strengths-threats (ST), namely ‘maintaining operational capabilities against cyber-attacks. In terms of weaknesses and threats (WT), a total of four development strategies has been identified, including ‘providing technology training to employees to protect against cyber risks. Addressing digitalization in Ro-Ro terminals through SWOT-FAHP analysis contributes to the literature and assists practitioners in establishing a strategic roadmap